HASIL DAN MUTU BENIH KEDELAI (Glysine max (L.) Merr.) DENGAN BUDIDAYA BASAH - I. G. N. Raka; W. Q. Mugnisjah; J. Wiroatmodjo; K. Idris (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 1995)
Field experiment for soybean seed production was carried out in Darmaga Experimental Station from June to September 1992. Three varieties of soybean, namely Lokon, Wilis, and Amerikana (early, middle, and late maturity, respectively) were planted both by saturated and conventional soil culture. Seed quality testing was carried out in the Laboratory of Seed science and Technology at IPB, Bogor, from September to October 1992. Yield components and seed production of the three varieties showed the same pattern in both saturated and conventional soil culture. Seed quality of Lokon and Wilis varietieswere higher than that of Amerikana in both cultivations. This was due to the less field weathering experienced by Lokon and Wilis varieties. Compared to the conventional soil culture, the saturated soil culture improved the yield components, seed production, and performance of seed physical and physiological quality of the three varieties.